1953
DOI: 10.1128/jb.66.2.245-246.1953
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Deviation From Linearity of the Thermal Death Rate Curve of a Putrefactive Anaerobe

Abstract: C for six days, centrifuged to remove the bulk of the organisms, and the supernatants subsequently filtered through Coors porcelain filters. Flocculation units and the minimum lethal dose for guinea pigs were determined on each culture TABLE 1 Effect of the addition of L-tyrosine to the medium TOXIN MG L-TYROSINE PER 100 ML MEDIUM Lf pr ml Minimum lethMl lethal dose doeper ml thai dos 0 80

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1957
1957
1966
1966

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This phenomenon has been encountered by several other investigators (Reynolds and Lichtenstein, 1952;Malin, 1952;El-Bisi and Ordal, 1956a). Kaplan, et al (1953) confirmed that the initial shoulder in their survivor curves of putrefactive anaerobe no. 3679 was real and not due to experimental error.…”
Section: Discussionsupporting
confidence: 73%
“…This phenomenon has been encountered by several other investigators (Reynolds and Lichtenstein, 1952;Malin, 1952;El-Bisi and Ordal, 1956a). Kaplan, et al (1953) confirmed that the initial shoulder in their survivor curves of putrefactive anaerobe no. 3679 was real and not due to experimental error.…”
Section: Discussionsupporting
confidence: 73%
“…For vegetative bacteria, this curve is most frequently described in terms of the D60 value and ZD, usually found to be about 5.6 + 1.1 C (15). Although the logarithmic nature of thermal killing is widely accepted, some workers, such as Kaplan et al (9) and Humphrey and Nickerson (8), have found significant deviations from this ideal with bacterial spores. White (18) and Elliker and Frazier (7) noted similar findings with nonsporeforming bacteria.…”
mentioning
confidence: 99%
“…Mlany of the data concerning the destruction of bacteria and their spores by deleterious agents have been presented with the assumption that the "logarithmic order of death of bacteria" has been adequately validated (Bigelow, 1921;Esty and Williams, 1924;Rahn, 1945a, b;Stumbo et al, 1950;Lee, 1953;Schmidt et al, 1955;El-Bisi and Ordal, 1956a, b). Some investigators, however, have reported data which do not agree with this point of view (Falk and Winslow, 1926;Williams, 1929; Davis and Williams, 1948;Reed et al, 1951;Sugiyama, 1951; Reynolds and Lichtenstein, 1952;Kaplan et al, 1953;La Baw and Desrosier, 1954). The concept of a logarithmic order of death has led to 1 Scientific Paper No.…”
mentioning
confidence: 99%